Management of oil and gas transportation system of Ukraine: new challenges - Дзьоба, О. Г.; Струк, Н. П. (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2014)
The article is summarized to the problems of functioning of the gas-transport system of Ukraine, it is substantiated the expediency of reformation in a globalized energy markets. The basic variants of effective management the gas-transport system are analysed. It is investigated real and potential benefits and threats of privatization or transfer its concession. They are offered near-term measures, necessary for an improvement managements of gas-transport the system.